KHULIA BHAORIA", A FOLK PERFORMING ART OF DARRANG (ASSAM) - Deepjyoti Baruah, Bikash Dewri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The civilization and individual existence of a community / Society being in a region can be determine from the art, plough and culture that particular region/extent. Art plough and culture all three phases originally comes from the similar concept. Briefly/in abridge form, exercise and repeated practice of a subject can be called as culture. The reformed and edited version of plough which is acceptable for the Society is culture and the glorious , splendid and eye catching form born from is Culture. Most of the art and culture of the world has created from folk individual or originated from folk society. It is recognise as a folk performing art. When arts are created by folk society, build itself to perform in front of a particular corporate population/society. In the honour of Assamese folk culture/ Darrang’s Khulia Bhaoria occupied a place of precious gem. In generally, this Art has been performing in Darrang District and its suburbs area. Taking reference from epics with visual and audible medium creates parole and scene. This folk element based Art is called "Khulia Bhauria